Anti-windup based dynamic output feedback controller design with performance consideration for constrained Takagi–Sugeno systems. (April 2015) - Nguyen, AnhTu; Dequidt, Antoine; Dambrine, Michel
Abstract: This paper proposes an LMI-based method to guarantee the closed-loop regional stability and performance for Takagi–Sugeno systems that are subject to input saturation, state constraints, and also amplitude-bounded disturbance. Based on the Lyapunov stability tool, the proposed method provides conditions to simultaneously design the dynamic output feedback controller and its anti-windup compensator. By solving a convex optimization problem, these conditions are derived such that a tradeoff between the upper bound on the nominal ℒ2 gain for exogenous disturbance and the minimal size of the domain of attraction can be found. This method is simple and systematic, allowing dealing with a very large class of constrained nonlinear systems. The effectiveness of the proposed method is illustrated with numerical examples.